Automatic DC capacitor reformation - Lim, Zhixiang (Nanyang Technological University, 2024)
This project "Automatic DC Capacitor Reformation" addresses the issue of DC capacitors aging and degrading over time as a critical component of electronic systems and power supplies. Over time, DC capacitors have the tendency to lose their effectiveness due to temperature variations, voltage stresses, and long-term usage. It is typically labor-intensive, time-consuming, and prone to error to reform capacitors using traditional methods.